Diversity and Virulence Profile of Aeromonasfrom potable water (BioMedical Research in Microbiology (BMR Microbiology) (ISSN: 2349-4603), 2024)
Aeromonas spp. are autochthonous in the aquatic ecosystem and some of them has been increasingly found, in patients with various diseases like enteritis, wound infection and even septicemia in amphibians, reptiles, frog, fish and in patients with impaired immunity. There are different virulence factors like aerolysin, hemolysins, cytotoxins, enterotoxins, proteolytic activity, lipolytic activity, gelatinase, slime production, DNases, and adhesions. These virulence factors are used as survival means, self defense mechanism and establishment of pathogenicity. They are also capable of forming biofilm and are found multiresistant, although free cells of Aeromonas may be relatively susceptible to disinfection; populations associated with biofilms may survive high chlorine dosing. Thus water distribution systems should be monitored to check the quality of water and for the purpose of public health